The Vermicidal Activity of Water Extract Two Types of Ethnopharmacology Against Haemonchus contortus in Kacang Goat (Capra hircus) In-vitro - I Gusti Komang Oka Wirawan; Suryawati -; Theresia Nur Indah Koni; Redempta Wea (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2022)
This research aims at determining the differences in the vermicidal activity between EADMAN and EADMDV in-vitro based on concentration and treatment time. It encompassed three groups of concentrations of EADMAN and EADMDV solution (2.5%, 3.5%, 4.5% from 0.2 g/mL each extract solution), a group of negative control (aqua pro injection), and a group of positive control (Oxfendazole 0.055%). The EADMAN and EADMDV was diluted in 1.5 mL aqua pro injection, then placed on petri dish with a concentration of 2.5%, 3.5%, 4.5% of 0.2 g/mL extract solution. Eight worms placed on each petri dish afterwards. The effectivity of EADMAN and EADMDV was determined based on the percentage of dead worms. The dead and live worms was counted from each immerse group for 1, 3, 5, 7 hours with four replications for each treatment. The vermicidal activity was indicated by touching the worms using a spatula; if it did not react, it was put in warm water. If the worms did not move, it was declared as the dead one, otherwise it was paralysed. Data of effective concentration from both extracts against vermicidal activity was analyzed using a two-way Anova, followed by Tukey test (P>0.05). The result showed the vermicidal activity of 2,5% EADMDV was significantly greater than 4.5% EADMDV, the negative control, and EADMAN at all concentrations. Meanwhile, its difference to 3.5% EADMDV and positive controls revealed insignificant results statistically. Therefore, 2.5% concentration of EADMDV with 7 hours of immersions gave the most effective vermicidal activity against Haemonchus contortus.